Hi,
This is in the form ag^2 + bg + c = 0, where a, b, and c are numbers
For the equation g^2 + 5g - 6 = 0, move the constant to the other side.
g^2 + 5g = 6
If the squared term had a coefficient other than 1, you would divide every term by that number. In this case, you don't need to do that.
Multiply 1/2 times the value of "b" . Square the result and add it to both sides.
1/2 x 5 = 5/2 (5/2)^2 = 25/4
g^2 + 5g + 25/4 =6 + 25/4
Factor the left side. Combine the right side.
(g + 5/2)^2 = 49/4
Take the square root of both sides. Put +/- in front of the radical on the right side.
sqrt[(g + 5/2)^2] = +/- sqrt[ 49/4]
g + 5/2 = +/- 7/2
Subtract 5/2 on both sides.
g = -5/2 +/- 7/2
g = -6 or 1
I hope that helps!! :-)
2007-05-13 07:49:32
·
answer #1
·
answered by Pi R Squared 7
·
0⤊
0⤋
First, get the constant on the other side.
g^2 + 5g = 6
Now we want to add a number so the left side becomes a perfect square. The trick for this is the number you add is (b/2)^2, where b is the number with the first power variable, in this case 5. So we add to both sides 25/4.
g^2 + 5g +25/4 = 6 +25/4
This simplifies to:
(g+5/2)^2=49/4
Square root both sides
g+5/2=+/- 7/2
Now solve for g for 7/2 and -7/2
g= 7/2 - 5/2 = 1
g= -7/2 - 5/2 = -6
(Of course, this is a lot easier by factoring, but that's not what you asked.) ; )
2007-05-13 07:54:16
·
answer #2
·
answered by Supermatt100 4
·
0⤊
0⤋
g^2 + 5g - 6 = 0
g^2+2*5/2 g+25/2-25/4-6=0
(g+5/2)^2=49/4
taking square roots of both sides
(g+5/2)=+ or -7/2
g=-6,1 answer
2007-05-13 08:07:25
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
g^2 + 5g - 6 = 0
(g+6) (g-1) = 0
g = -6 or g= 1
2007-05-13 07:59:31
·
answer #4
·
answered by Chow 2
·
0⤊
0⤋
g^2 + 5g + (5/2)^2 = 6 + (5/2)^2
(g + 5/2)^2 = 49/4
Either
g + 5/2 = 7/2 ===> g = 1
Or
g + 5/2 = - 7/2 ===> g = -6
2007-05-13 07:41:01
·
answer #5
·
answered by a_ebnlhaitham 6
·
0⤊
0⤋
HI. you need to factor it. (g+6)(g-1)=0. So g can = -6 or 1.
2007-05-13 07:39:14
·
answer #6
·
answered by Rob M 1
·
0⤊
0⤋
g^2+5g-6=0
g^2+6g-g-6=0
g(g+6)-1(g+6)=0
(g-1)(g+6)=0
(g-1)=0,(g+6)=0
g=1,g= -6
2007-05-13 07:41:07
·
answer #7
·
answered by chapani himanshu v 2
·
0⤊
0⤋
(g + 6)(g - 1) = 0
g = -6, g = 1
.
2007-05-13 07:43:09
·
answer #8
·
answered by Robert L 7
·
0⤊
0⤋